Ketimpangan Gender Dalam Keputusan Rumah Tangga: Studi Interseksi Ekonomi, Pendidikan, dan Konstruksi Sosial - Ivan Nurseha (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2024)
This study aims to analyses gender inequality in household decision-making by looking at the intersection between economic, educational, and social construction factors. Using a qualitative approach with case study and phenomenological methods, this research was conducted in Tuban, East Java, which was chosen for its diverse social strata and local culture. Data were collected through in-depth interviews, focus group discussions (FGDs), participatory observation and supporting surveys, with the subjects being household couples from various socio-economic backgrounds. The results show that household decisions, particularly those related to finance, are still dominated by men, although women also have significant economic contributions. Educational factors were shown to play an important role in improving gender equality, with highly educated couples showing more equal decision-making patterns. However, traditional cultural norms remain a major barrier for women to fully participate in decision-making, especially among couples with low education and limited income. In addition, the study found a changing pattern among young couples, especially in urban areas, which showed a trend towards more equal sharing of responsibilities. The complexity of interactions between economic, educational and social construction factors emphasizes the need for an intersectional approach in understanding the dynamics of gender inequality at the household level. The study concludes that efforts to reduce gender inequality should include improving access to education for women, economic empowerment, and transforming social norms that limit women's roles. The findings provide relevant insights to support more inclusive gender equality policies at the local and national levels.